DETERMINANT OF PERSONAL HYGIENE BEHAVIOR OF ONLINE MOTORBIKE TAXI DRIVERS IN COVID 19 PREVENTION IN SEMARANG CENTRAL JAVA - Sekar Putranti Widantari; Nur Endah Wahyuningsih; Nikie Astorina Yunita Dewanti (Jurnal Riset Kesehatan, 2021)
Online motorcycle taxi drivers are at risk of contracting COVID-19 because they have a high frequency of contact with other people and objects that have the possibility of SARS-CoV 2 on their surface. This study aims to determine the determinants of personal hygiene in online motorcycle taxi drivers in an effort to prevent COVID-19 in the city of Semarang, which is an analytical observational study using a cross-sectional approach. The sample in this study were 385 drivers who were in the online motorcycle taxi driver communities on Facebook and Twitter. The sampling technique uses a snowball, and the research instrument is a questionnaire distributed via google forms. Data analysis using Chi-Square Test. 89.4% of online motorcycle taxi drivers are male, 76.1% have low levels of education, 58.7% have low-income levels, 32.2% have poor knowledge, 46.2% have poor attitudes, 48.3% had poor family support, 26.2% had poor peer support, 45.2% had poor information accessibility, and 47% had poor personal hygiene behavior. There is a relationship between knowledge (p-value less than 0.001) attitude (p-value less than 0.001 ) and family support (p-value less than 0.001 ) with personal hygiene behavior. Knowledge becomes the most influential determinant of personal hygiene behavior. Providing an educational menu in the driver application can help to increase knowledge.